Upaya Meningkatkan Motivasi dan Hasil Belajar Siswa Kelas XI SMK Wikarya Karanganyar dengan Gamifikasi pada Mata Pelajaran Manajemen Perkantoran - Zahidah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to describe the application of online gamification strategies in enhancing the learning motivation of Grade XI MPLB students at SMK Wikarya Karanganyar in the subject of Office Management, specifically the Human Resource Management (HRM) component. This study is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of planning, observation, action, and reflection. The research subjects were 27 students in the 11th grade of SMK Wikarya for the 2024/2025 academic year. Data collection techniques included observation, learning motivation questionnaires, interviews, and documentation. Data analysis was conducted using descriptive comparative techniques and qualitative analysis. The validity testing techniques used were data source triangulation and reliability validity testing. The research results indicate that the implementation of online gamification can enhance students' learning motivation. This is evidenced by an increase in the average learning motivation score from 65.13 before the intervention to 68.40 in Cycle I, rising to 74.62 in Cycle II, and further increasing to 78.14 in Cycle III. Students became more active, enthusiastic, and demonstrated greater interest in learning. Challenges faced include limitations in information and communication technology devices and time constraints in classroom management. Solutions implemented include expanding internet connectivity with a Wi-Fi extender, providing detailed explanations of learning activities, simplifying learning materials, and strengthening time management. The conclusion of this study indicates that the implementation of online gamification can significantly enhance students' learning motivation. Teachers are advised to consider using gamification as an innovative and engaging learning strategy in today's digital age.